Preparación de los docentes sobre la inclusión y atención a la diversidad en la educación inicial básica - Landazuri Obando, Mariuxi Elizabeth (2019)
The movement of inclusion in the educational field has led to a series of questions about how to promote it properly within a classroom. It has been shown that the preparation of teachers is of utmost importance in the implementation of the principles of inclusive education and attention to diversity. Within the classrooms, the diversity of children who have specific educational needs has increased. It is essential to promote positive attitudes in students from an early stage to accept diversity, so that currently heterogeneous groups are more common in educational institutions……